Assessing the impact of algorithmic trading on markets: A simulation approach - Markus Gsell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Innovative automated execution strategies like Algorithmic Trading gain significant market share on electronic market venues worldwide, although their impact on market outcome has not been investigated in depth yet. In order to assess the impact of such concepts, e.g. effects on the price formation or the volatility of prices, a simulation environment is presented that provides stylized implementations of algorithmic trading behavior and allows for modeling latency. As simulations allow for reproducing exactly the same basic situation, an assessment of the impact of algorithmic trading models can be conducted by comparing different simulation runs including and excluding a trader constituting an algorithmic trading model in its trading behavior. By this means the impact of Algorithmic Trading on different characteristics of market outcome can be assessed. The results indicate that large volumes to execute by the algorithmic trader have an increasing impact on market prices. On the other hand, lower latency appears to lower market volatility.
urn:nbn:de:hebis:30-62284
Keywords: G10; 330; Algorithmic Trading; Simulation; Double Auction; Wertpapierhandel; Elektronisches Handelssystem; Auktionstheorie; Simulation; Börsenkurs; Volatilität; Theorie